2018
DOI: 10.1002/hep.29872
|View full text |Cite
|
Sign up to set email alerts
|

Host and viral factors associated with serum hepatitis B virus RNA levels among patients in need for treatment

Abstract: Hepatitis B virus (HBV) RNA in serum is a novel biomarker for intrahepatic HBV replication and treatment response. For its proper use, it is essential to identify factors influencing serum HBV RNA level. Using a rapid amplification of complimentary DNA (cDNA) ends (RACE) PCR technique (lower limit of detection [LLD], 800 copies/mL [c/mL]), serum HBV RNA levels were measured in samples of 488 untreated individuals with chronic HBV infection who were eligible to treatment according to currently used recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
93
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 22 publications
15
93
6
Order By: Relevance
“…Indeed, this finding was also highly consistent with the result of the correlation analysis. In previous studies, HBV genotypes, serum HBV DNA levels and liver histological changes were reported to be associated with the levels of serum HBcrAg, HBsAg or HBV RNA . However, they had no significant association with intrahepatic cccDNA levels among HBeAg‐positive patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this finding was also highly consistent with the result of the correlation analysis. In previous studies, HBV genotypes, serum HBV DNA levels and liver histological changes were reported to be associated with the levels of serum HBcrAg, HBsAg or HBV RNA . However, they had no significant association with intrahepatic cccDNA levels among HBeAg‐positive patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For untreated patients, the correlation coefficient of serum HBV pgRNA and DNA is higher in hepatitis B e antigen (HBeAg)–negative patients than HBeAg‐positive patients ( r = 0.741 and r = 0.532, P < 0.001, respectively) . However, van Campenhout et al reported a comparable correlation of serum HBV flRNA to DNA between HBeAg‐positive and HBeAg‐negative patients ( r = 0.72 and r = 0.78, P < 0.001, respectively) . Such a discrepancy may be due to the differences in the number of subjects and/or patient characteristics.…”
Section: Correlation Between Serum Hbv Rna and Other Hbv Markersmentioning
confidence: 99%
“…RACE‐based real‐time quantitative PCR using specific primers designed for reverse transcription, according to Kairat et al, was later developed to selectively quantify serum 3′ full‐length polyadenylated HBV RNA (flRNA) and 3′ internally‐truncated polyadenylated HBV RNA (trRNA). The RACE–quantitative PCR–based flRNA quantification has been widely employed in recent studies . In addition to RACE–quantitative PCR, regular quantitative RT‐PCR methods with HBV‐specific primers targeting the X, C, or S region of the HBV genome were developed to quantify serum HBV RNA .…”
Section: Serum Hbv Rna Species and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV RNA is the reverse transcriptional template of the negative strand of HBV DNA . Serum HBV DNA and HBV RNA are significantly associated with cccDNA in treatment‐naïve patients with chronic HBV infection as well as in HBeAg‐positive mice models . The amount of HBV RNA in the serum of treatment‐naïve patients is approximately 10 6 copies/mL, while HBV DNA is up to 10 9 copies/mL.…”
Section: Application Of Viral Markers In Chb Clinical Practicementioning
confidence: 99%